Writing the Victorian Constitution - Ward, Ian (Palgrave Modern Legal History, 2018)
This book charts the writing of the English constitution through the work of four of the most influential jurists in the history of English constitutional thought-Edmund Burke, Thomas Babington Macaulay, Walter Bagehot and Albert Venn Dicey. Stretching from the French Revolution to the death of Queen Victoria, their writing is both representative of and formative to the Victorian constitution. Ian Ward traces how constitutional writing changed over the course of the long nineteenth century, from the poetics of Burke and the romance of Macaulay, to the pragmatism of Bagehot and the jurisprudence of Dicey. A century on, our perception of the English constitution is still shaped by this contested history.